Two new species of Stilbochaeta (Chaetosphaeriaceae, Chaetosphaeriales) from freshwater and terrestrial habitats in China - Wangming Zhang; Qinying Feng; Xiaoyu Song; Xinzhong Zhou; Wanqing Xie; Juan Lu; Li Lu (MycoKeys)
During a taxonomic investigation of saprobic fungi in the tropical and subtropical regions of southern China, four hyphomycetous isolates were obtained from freshwater and terrestrial substrates. Phylogenetic analyses, based on combined LSU and ITS rDNA sequence data, coupled with detailed morphological comparisons, revealed that two of the isolates represent previously undescribed species within the genus Stilbochaeta. The new taxa, Stilbochaeta guizhouensis and S. hainanensis, are introduced herein with comprehensive descriptions and illustrations. The present study expands the known diversity of Stilbochaeta and enhances the understanding of asexual fungal taxa in both aquatic and terrestrial ecosystems in China.